The difficulty of translating collocations from Arabic into English encountered by a sample of Arab students - Jabak, Omar Osman; Syed Abdullah, Syed Nurulakla; Mustapha, Nik Farhan (Pusat Pengajian Teras, Kolej Universiti Islam Antarabangsa Selangor, 2016)
The present study aimed at exploring the difficulty that was encountered by a sample of Saudi undergraduate students when they translated collocations from Arabic into English. The researchers attempted to identify the reasons behind such a difficulty and find practical solutions to this difficulty. They followed an experimental descriptive method in the study. They also designed a quiz on collocations and administered it to the students as part of the requirements of a course the students were taking at that time. The quiz was given to 50 Saudi undergraduate students at the Department of English at Teachers College of King Saud University in the second semester of the academic year 20015. The quiz consisted of 15 Arabic sentences which apparently included collocations. The research data and findings revealed that the majority of the students could not translate collocations correctly because they adopted literal translation, used bilingual dictionaries and had very little knowledge of the concept of collocations in both languages. To help Arab students overcome this enormous difficulty, the researchers offered some recommendations and suggestions at the end of their study.